Portable Tidal Monitoring System for Coastal Observation in North Sulawesi - Christian Mala; Alfet Luasunaung; Patrice Kalangi; Robert Bara; Rosita Lintang; Stephanus Mandagi; , Deiske A. Sumilat; Intan Pangerti (JURNAL PESISIR DAN LAUT TROPIS, 2025)
Tidal data play a critical role in supporting maritime weather forecasting and providing disaster-related information, such as early warnings for tidal flooding. However, the limited distribution of tide gauge instruments across Indonesia remains a significant challenge in obtaining comprehensive data. This study aims to design and implement a portable tidal measurement device as an alternative solution to enhance data availability. The system is developed to monitor sea level heights in the operational area of the Bitung Maritime Meteorological Station, North Sulawesi, utilizing a JSN-SR04T ultrasonic sensor as the primary measurement instrument. The collected data are transmitted wirelessly using an ESP8266 NodeMCU module connected to the internet via a modem, subsequently stored in a database, and displayed through an Internet of Things (IoT)-based user interface. The device calibration was conducted by comparing the prototype’s measurements with those obtained from the standard Automatic Weather Station (AWS) at Bitung Maritime Station. Performance testing was carried out at Manado Port from October 5,2022 to October 7, 2022 2022. The observational data were validated using the Root Mean Square Error (RMSE) method to evaluate measurement accuracy. Validation results indicate that the closer the RMSE value approaches zero, the higher the accuracy of the data produced. Keywords: tidal monitoring, internet of things, ultrasonic sensor ABSTRAK Data pasang surut laut merupakan komponen krusial dalam mendukung prediksi cuaca maritim serta penyediaan informasi kebencanaan, seperti peringatan dini banjir rob. Namun demikian, keterbatasan distribusi alat pengamatan pasang surut di Indonesia masih menjadi kendala dalam memperoleh data yang komprehensif. Penelitian ini merancang dan mengimplementasikan perangkat pengukur pasang surut portabel sebagai solusi alternatif untuk meningkatkan ketersediaan data. Sistem dirancang untuk memantau ketinggian muka air laut di wilayah Stasiun Meteorologi Maritim Bitung, Sulawesi Utara, dengan memanfaatkan sensor ultrasonik JSN-SR04T sebagai alat ukur utama. Data hasil pengukuran dikirim secara nirkabel menggunakan modul ESP8266 NodeMCU yang terhubung ke jaringan internet melalui modem, kemudian disimpan dalam basis data dan ditampilkan melalui antarmuka berbasis Internet of Things (IoT). Kalibrasi perangkat dilakukan dengan metode komparatif terhadap alat standar Automatic Weather Station (AWS) Maritim Bitung. Uji performa perangkat dilaksanakan di Pelabuhan Manado selama 5 Oktober hingga 7 Oktober 2022. Data hasil pengamatan divalidasi menggunakan metode Root Mean Square Error (RMSE) untuk mengukur tingkat akurasi. Hasil validasi menunjukkan bahwa semakin mendekati nilai nol pada RMSE, maka tingkat akurasi data semakin tinggi. Kata kunci: pasang surut laut, internet of things, sensor ultrasonic